PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN, IMPLEMENTASI SISTEM INFORMASI MANAJEMEN DAERAH, DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (STUDI KASUS DI KOTA MADIUN) - Kristin Denada; Siti Suharni; Andri Hasmoro Kusumo Broto (JAMER : Jurnal Akuntansi Merdeka, 2024)
Abstract- This research aims to examine the effect of implementing government accounting standards, implementing regional management information systems and human resource competence on the quality of regional government financial reports. This type of research is quantitative. The data collection technique in this research uses questionnaires directly to respondents. The respondents in this study were employees of the Madiun City Regional Revenue Agency. Data analysis was carried out using multiple linear regression analysis with the SPSS (Statistical Product and Service Solution) version 25 for Windows program. The results of the hypothesis research show that the Implementation of Government Accounting Standards variable is 0.022, the Regional Management Information System Implementation variable is 0.004, the Human Resources Competency variable is 0.031 and the Adjusted R Square shows a value of 0.626 or 62.6%. The results of this research show that the implementation of government accounting standards has a positive influence on the quality of regional government financial reports, the implementation of regional management information systems has a positive influence on the quality of regional government financial reports, and human resource competence has a positive influence on the quality of regional government financial reports.